2009
DOI: 10.1016/j.cellbi.2009.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Gene networks involved in apoptosis induced by hyperthermia in human lymphoma U937 cells

Abstract: To define the molecular mechanisms that mediate hyperthermia-induced apoptosis, we performed microarray and computational gene expression analyses. U937 cells, a human myelomonocytic lymphoma cell line, were treated with hyperthermia at 42 degrees C for 90 min and cultured at 37 degrees C. Apoptotic cells ( approximately 15%) were seen 6 h after hyperthermic treatment, and elevated expression of heat shock proteins (HSPs) including Hsp27, Hsp40, and Hsp70 was detected, following the activation of heat shock fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 44 publications
(68 reference statements)
2
19
0
Order By: Relevance
“…The PCR amplification was analyzed by real-time PCR. The detailed conditions of PCR were described in our previous study [31]. The annealing temperature of RANK, RANKL, and -actin was 60 °C.…”
Section: Expression Analyses Of Rank and Rankl Mrnas In Fugu Pth1 (1-mentioning
confidence: 99%
See 1 more Smart Citation
“…The PCR amplification was analyzed by real-time PCR. The detailed conditions of PCR were described in our previous study [31]. The annealing temperature of RANK, RANKL, and -actin was 60 °C.…”
Section: Expression Analyses Of Rank and Rankl Mrnas In Fugu Pth1 (1-mentioning
confidence: 99%
“…The annealing temperature of PTH1R and PTH2R was 60 °C. The detailed conditions of PCR were described in our previous study [31].…”
Section: Comparison Of Pth1r and Pth2r Mrna Expression In The Scalesmentioning
confidence: 99%
“…Recent DNA microarray and computational microarray analyzing technologies have provided a view of the expression (9,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). It is well known that cancer cells exposed to HT of more than 42.5˚C will undergo cell death, whereas exposure to MHT conditions, i.e., temperatures up to 42.5˚C, produces only slight or no cytotoxicity (26).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the mobility shift of HSF1 due to its phosphorylation indicates the activation of the molecule (31). In U937 cells, the elevated expression of HSPs such as Hsp70, Hsp40 and Hsp27 was observed following the activation of HSF1 under both non-apoptotic and apoptotic conditions (19,26). At 42˚C for 15 min, a transient mobility shift of HSF1 was observed at 0 and 0.5 h after the treatment.…”
Section: Resultsmentioning
confidence: 94%
“…Several investigators have indicated that heat stress affects the expression pattern of genes in many kinds of cell types with a cell death or no cell death condition (17-27). In addition, bioinformatics analysis have shown that differentially expressed genes influenced by heat could be sorted into several functional categories such as molecular chaperones, cell death, protein degradation, transcription, signal transduction and membrane transport (10,17,19,22,23,26). As described above, because heat stress induces complex cellular responses and changes in signal transduction, the mechanisms of heat response have not been elucidated in detail.…”
Section: Introductionmentioning
confidence: 99%